2021
DOI: 10.3390/jcm10225310
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Prader-Willi Syndrome: Natural History during the Transition from Childhood to Adulthood in a Cohort of 39 Patients

Abstract: Type 2 diabetes mellitus (T2DM) affects 20% of patients with Prader-Willi syndrome (PWS), with many cases diagnosed during the transition period. Our aim was to describe the natural history of T2DM in patients with PWS before the age of 25 years and to develop screening and preventive strategies. Thirty-nine patients followed in the French PWS Reference Center were included (median age 25.6 years [23.7; 31.7]). Twenty-one had been treated with growth hormone (GH), fifteen had not, and three had an unknown stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…High leptin resistance may result in excessive eating. Further studies on a larger number of cases are needed to establish whether the treatment of diabetes is difficult in TS 14 patients complicated by T2DM, similar to patients with Prader-Willi syndrome complicated by T2DM (29).…”
Section: Discussionmentioning
confidence: 99%
“…High leptin resistance may result in excessive eating. Further studies on a larger number of cases are needed to establish whether the treatment of diabetes is difficult in TS 14 patients complicated by T2DM, similar to patients with Prader-Willi syndrome complicated by T2DM (29).…”
Section: Discussionmentioning
confidence: 99%
“…This prohormone convertase is less well studied, and mutations in PCSK2 are commonly associated with impaired glucose homeostasis in the context of type 2 diabetes [ 63 , 64 , 65 ]. The PWScr m+/p− mice have a mostly normal glucose metabolism, while human PWS patients are thought to suffer from type 2 diabetes, especially in the late stage of disease progression, typically due to severe obesity [ 6 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of type 2 diabetes is reported to be 0 to 25% depending on the study population ( 34 , 47 , 58-60 ). A recent study showed that diabetes in young, obese adults was diagnosed at a mean age of 16 years with a peak during the transition period, suggesting reinforced glucose monitoring in adolescents and young adults ( 61 ). Insulin resistance and obesity are well known risk factors for type 2 diabetes and higher insulin levels and a high homeostatic model assessment index has been demonstrated in obese compared with nonobese adults with PWS ( 34 , 59 , 60 ).…”
Section: Insulin and Diabetesmentioning
confidence: 99%